Skrining Aktivitas Antibakteri, Fitokimia & Antioksidan Ekstrak Etil Asetat Batang Tumbuhan Kitolod (Isotoma longiflora) - Luh Putu Ardha Gangga Cendani; Anak Agung Gede Indraningrat; Marta Setiabudy (Aesculapius Medical Journal, 2025)
Bacterial infectious disease is a condition when pathogenic bacteria enter the human body and cause disease. Cases of bacterial infections are getting worse with the increase in bacterial strains that develop antibiotic resistance. Efforts to overcome the problem of bacterial infections are by exploring herbal plants with antibacterial abilities. One of the herbal plants that has the potential to be researched is the stem of the kitolod plant (Isotoma longiflora). Empirically, this plant has been used by traditional communities to treat bacterial infections, but there has not been much research that can provide comprehensive information regarding the metabolite compounds contained in kitolod stems. This research used 100 grams of dry samples of kitolod stems which were macerated using 500 ml of ethyl acetate solvent (1:5, w/v) for 24 hours and remaceration was carried out once. The macerate obtained was evaporated using a rotary evaporator at a temperature of 40oC to get a thick extract from kitolod stems. The extract was tested in triplicate against gram-negative bacteria Escherichia coli (ATCC 25922), Klebsiella pneumoniae (ATCC 700603) and Gram-positive Streptococcus mutans (FNCC 0405), Staphylococcus aureus (ATCC 25923) using method Kirby-Bauer. The phytochemical content of kitolod stem extract was tested to detect the presence of flavonoids, alkaloids, tannins and saponins. The antioxidant activity of kitolod stem extract was tested using the DPPH method (2,2-diphenyl-1-picrylhidrazyl). The results of phytochemical screening show that kitolod extract contains flavonoids, alkaloids and saponins. Atibacterial activity screening showed that no inhibition zone was formed against Gram-positive or Gram-negative test bacteria. The antioxidant test showed that the ethyl acetate extract of kitolod stems had very weak antioxidant levels, namely at the IC value50 393847.22 ppm and 2752.9442 ppm. Further research will be focused on extracting kitolod stems using several different organic solvents, so that the bioactivity of kitolod can be more explored.